Salidroside Ameliorates Cardiomyocyte Hypertrophy by Upregulating Peroxisome Proliferator-Activated Receptor-α - Gao, Hui; Tian, Kunming; Meng, Yichong; Liu, Xueping; Peng, Yingfu (Frontiers in Pharmacology, 2022)
Cardiac hypertrophy is an adaptive change in response to pressure overload, however the hypertrophy may evolve toward heart failure if cannot be corrected as soon as possible. The dysfunction of peroxisome proliferator-activated receptor-α (PPARα) plays a key role in cardiac hypertrophy. In the present study, salidroside inhibited the mRNA expressions of hypertrophic markers including atrial natriuretic factor and brain natriuretic peptide in a dosage-dependent manner. Furthermore, the protein expression and transcriptional activity of PPARα were increased by salidroside in H9C2 cells treated with angiotensin II, as well as the target genes of PPARα, while the situations were nearly reversed when PPARα was knocked down. Next, salidroside could elevate the expression of ATGL, a key upstream regulator of PPARα; the effects of salidroside including increasing PPARα function and inhibiting cardiomyocyte hypertrophy were impaired by ATGL knockdown. Our present studies suggested that salidroside elevated PPARα function to alleviate cardiomyocyte hypertrophy, which was involved in the increase of ATGL expression.